Plastic Marine Pollution in the Gulf of Maine - Law, Kara; Donohue, Jessica; Miller, Rachael (Maine Policy Review, 2023)
Plastic pollution is a leading environmental issue because of its demonstrated and potential harms to wildlife, as well as to ecosystem and human health. The Gulf of Maine has already suffered ecological shifts due to recent unprecedented warming of ocean waters, with consequences to coastal economies that rely on ecosystem services. Here, we explore the prevalence of plastic pollution as a potential compounding threat to Gulf of Maine ecosystems by analyzing microplastics and plastic debris collected in surface-towed plankton nets since 1987. Although we find low concentrations of small floating plastic particles, 20 years of coastal and remote-island shoreline cleanup activities demonstrate the continued accumulation of large plastic debris. Policies to address plastic pollution in the Gulf of Maine could strive to minimize littering or at-sea disposal, while also supporting environmental cleanup.
Keywords: plastic pollution; ocean; Gulf of Maine; plastic debris